Use of Fluoride and Silver Ion Compounds in Three International School Based Oral Health Programs – A Case Report - Steven R. Duffin; Marcus L. Duffin (Journal of Public Health International, 2020)
Untreated dental caries in children is one of the most common diseases and largest public health problems in the world. A novel caries management program, using 50% silver nitrate, 38% silver diamine fluoride, and 5% sodium fluoride varnish, was developed at Shoreview Dental, LLC, a private dental practice in Oregon USA, and then introduced into schools in Ecuador, Ghana, and Bolivia. Cavitated carious lesions were treated with 50% silver nitrate, followed by covering with 5% sodium fluoride varnish, three times over two weeks for 165 children in Ecuador at initial assessment, 3 months, and 6 months. This protocol was repeated for 271 children in Ghana at initial assessment and 12 months. In Bolivia, 130 children were treated with 38% silver diamine fluoride, followed by covering with 5% sodium fluoride varnish, once per visit at initial assessment, 6, 12, 18, 24, 30, and 36 months. The percentage of children with active cavitated carious lesions at initial evaluation was 92.7% (Ecuador), 55.4% (Ghana), and 92.3% (Bolivia). The final arrest rate of treated surfaces was 98.8% (Ecuador), 67.6% (Ghana), and 90.2% (Bolivia). Effectiveness of cavitated caries lesion arrest is increased when it is thoroughly cleaned and dried before the treatment protocol. Further optimization is obtained when this protocol is repeated multiple times.
Keywords: case report